PEMANFAATAN DASAR-DASAR JURNALISTIK DALAM MEMBANGUN MEDIA SEKOLAH DIGITAL UNTUK PEMBELAJARAN JURNALISTIK DI SMK 1 SETU - Egi Zahra, Mutiya; Juliandra, Luthpiyah; Nadhirah, Yuha (Universitas Islam 45 Bekasi, 2025)
The lack of journalism-based learning media in schools limits students' ability to develop journalistic skills and media literacy. This program aims to establish a digital school media platform at SMK 1 Setu as a learning tool. The implementation method includes observation, digital media design, journalism training, and evaluation through pre-test and post-test assessments. The results show a significant improvement in students' understanding of journalism, as indicated by their ability to write news, conduct interviews, and manage digital content. In conclusion, this program successfully enhances students' journalistic competencies and is recommended for sustainability through the formation of a school journalism team.